Teaching french poetry in the 16th century : : desingning the reading of the poem Sur la mort de Marie (1578) by Pierre de Ronsard (1524-1585) - Xypas, Rosiane (The ESPecialist, 2024)
Poetry reveals different actions and feelings in the universal themes discussed. However, its reading does not happen without resistance in an academic universe oriented towards the functional and useful. Thus, how to mobilize a poetic reading-reception that is remarkable for the reader? The objective of this article is to present the reception of the reading of the poem Sur la mort de Marie (1578) by Ronsard (1524-1585) developed through drawings that rely on the reader's procedural knowledge. Results point to a transmodal creation in the reception of the read poem, favoring greater student involvement, thanks to a methodological option, which opts for writing about what was read.